Incidence of the harvesting age on postharvest characteristics behavior of dominico hartón plantain (musa aab simmonds) (2012)
In this study a physical, chemical and physiological characterization of Dominico Hartón plantain grown in the Belalcázar municipality (Department of Caldas, Colombia) during harvest and postharvest was carried out. The research was performed with fruits of 14, 16 and 18 weeks after flowering. Every two days until senescence changes in weight, firmness, parameters of color L*a*b*, pulp/peel ratio, maturity index, pH, humidity, starch, respiration rate and ethylene rate were measured. This study used a longitudinal repeated measures design, balanced, with a three-level factor. The factor evaluated was harvesting time and the response variables were the physicochemical parameters. The results showed variation in weight near to 7%, the tint color parameter was between -61.46 and 86.74, chroma between 26.31 and 37.11 and ΔE of 1.4603 to 8360, the pH ranged from 6.2 to 3.98, pulp/peel of 2.53 to 4.11, the relationship °Brix/acidity of 11.36 to 26.2, humidity content between 60.56% and 56%, starch between 51.7% and 67% DM, the CO2 production rate between 3.4 and 8.9 g/kg.h, ethylene from 24 to 225 μL/kg.h. The maturation parameters showed climacteric behavior and total days to ripening were 9, 14 and 21 for the fruits of 18, 16 and 14 weeks from flowering.